2018
DOI: 10.1111/jsr.12696
|View full text |Cite
|
Sign up to set email alerts
|

The effects of maternal risk factors during pregnancy on the onset of sleep difficulties in infants at 3 months old

Abstract: Sleep problems in young children are among the most common concerns reported to paediatricians. Sleep is thought to have important regulatory functions, and sleep difficulties in early childhood are linked to several psychosocial and physiological problems. Moreover, several prenatal factors have been found to influence infants' sleep. Among them, most of the studies have been focused on maternal prenatal depression and/or anxiety as potential risk factors for sleep problems in childhood, whereas other relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 41 publications
5
23
1
Order By: Relevance
“…Some prenatal factors, such as mood disturbances [37] and/or substance exposure [38] have been reported to associate with sleep quality in the offspring. Moreover, we recently reported that symptoms of mood disturbances, ADHD and stress in mothers during pregnancy were associated with certain sleep difficulties and sleep practices at the age of three months [28]. Of note, in that study, infants' circadian rhythm development was not related to maternal prenatal risk factors, while the present study indicated that it is related to maternal circadian preference consistently across different time-points.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Some prenatal factors, such as mood disturbances [37] and/or substance exposure [38] have been reported to associate with sleep quality in the offspring. Moreover, we recently reported that symptoms of mood disturbances, ADHD and stress in mothers during pregnancy were associated with certain sleep difficulties and sleep practices at the age of three months [28]. Of note, in that study, infants' circadian rhythm development was not related to maternal prenatal risk factors, while the present study indicated that it is related to maternal circadian preference consistently across different time-points.…”
Section: Discussioncontrasting
confidence: 46%
“…These factors include inherited child's characteristics, such as temperament [24] or chronotype [19], perinatal characteristics such as season of birth [25] or photoperiod [26], and environmental characteristics such as parental stress [27]. Following this line of research, our recent study reported that some maternal risk factors during pregnancy are related to infants' sleep difficulties at three months of age [28]. Specifically, we found that symptoms of depression, Attention-Deficit Hyperactivity Disorder (ADHD), and stress in mothers during pregnancy were associated with such sleep difficulties as short sleep and long sleeponset latency, and sleep practices, such as co-sleeping with parents and irregular sleep routines, in three-month-old infants.…”
Section: Introductionmentioning
confidence: 97%
“…11 However, because ADHD does have a hereditary component, parental ADHD and/or other psychiatric risk factors may also negatively affect sleep during infancy. 13,14…”
mentioning
confidence: 99%
“…Finally, a recent study reported that several maternal risk factors during pregnancy were related to sleep difficulties in infants. 52 In relation to children, in a study conducted including 182 families, bedtime behavior and daytime sleepiness seemed to be greatly affected in those children of mothers with mental health problems. 53 …”
Section: Methodsmentioning
confidence: 99%